2023
DOI: 10.1007/s13167-023-00316-6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysregulation in glaucoma: retinal vasoconstriction and normal neurovascular coupling in altitudinal visual field defects

Abstract: Purpose Vision loss in glaucoma is not only associated with elevated intraocular pressure and neurodegeneration, but vascular dysregulation (VD) is a major factor. To optimize therapy, an improved understanding of concepts of predictive, preventive, and personalized medicine (3PM) is needed which is based on a more detailed understanding of VD pathology. Specifically, to learn if the root cause of glaucomatous vision loss is of neuronal (degeneration) or vascular origin, we now studied neurovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 85 publications
0
3
0
1
Order By: Relevance
“…30 Another study revealed that peripapillary arteriolar and venular tortuosity, arteriolar branching angle, circumpapillary vessel density, and circumpapillary fractal dimension were reduced in eyes with POAG. 31 A recent study by Zhou and Sabel 32 showed a significant decline in the diameter of retinal arterial and venous vessels in patients with POAG compared with healthy individuals using a dynamic vessel analyzer. They proposed that vascular dysregulation in POAG may be attributable to chronic vasoconstriction, which hinders the energy supply to retinal neurons and eventually results in neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%
“…30 Another study revealed that peripapillary arteriolar and venular tortuosity, arteriolar branching angle, circumpapillary vessel density, and circumpapillary fractal dimension were reduced in eyes with POAG. 31 A recent study by Zhou and Sabel 32 showed a significant decline in the diameter of retinal arterial and venous vessels in patients with POAG compared with healthy individuals using a dynamic vessel analyzer. They proposed that vascular dysregulation in POAG may be attributable to chronic vasoconstriction, which hinders the energy supply to retinal neurons and eventually results in neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of this study is that there was no difference in the venular parameters between POAG patients and the normal group. However, the diameter of the retinal arteriole decreased significantly, indicating that the pressure in the retinal vessel and outflow resistance increased [36] . This may reflect the relationship between glaucoma and the increased frequency of retinal vein occlusion.…”
Section: Correlation Analysis Of Retinal Arteriole Parameters With Rn...mentioning
confidence: 98%
“…Eine neue Perspektive gelang mit der Erkenntnis, dass beim Glaukom nicht nur oder sogar weniger die Arteriosklerose und ihre Risikofaktoren entscheidend sind, sondern eine vaskuläre Dysregulation, und zwar vor allem die primäre Form der vaskulären Dysregulation (PVD) 2 . Diese Hypothese wurde zuerst von J. Flammer und Mitarbeitern formuliert 17 und anschließend von mehreren Gruppen bestätigt 18 , 19 , 20 , 21 , 22 .…”
Section: Ursache Der Durchblutungsstörung Beim Glaukomunclassified